Marketing terytorialny w zarządzaniu rozwojem miast na przykładzie Gdańska, Krakowa, Poznania oraz Wrocławia - Dylik, Beata (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2017)
The creation of an image is an action which effects could be measured only in long-term perspective. In spite of that, the promotional trend is getting stronger and local authorities are allocating more and more funds for this purpose. That is the reason why territorial marketing is an essential implement for the management of urban development.